Susan Eckstein, The Poverty of Revolution. The State and the Urban Poor in Mexico, Princeton, Princeton University Press, 1977 - Guzmán, Marco V. (Estudios Demográficos y Urbanos, 1978)
Susan Eckstein, The Poverty of Revolution. The State and the Urban Poor in México, Princeton, Princeton University Press, 1977.